Fikih Muamalah dalam Konteks Pengelolaan Zakat, Infak, dan Sedekah Berbasis Star-Up Kitabisa.com - Insan, Niya Amalia; Wahyudi, Wahyudi (Institut Agama Islam Sunan Giri Ponorogo, 2021)
Generosity in Islam, which includes broad dimensions of goodness such as zakat, infak, alms, and waqf are terms that denote the official form of Islamic philanthropy. Kitabisa.com is a website for online donations and fundraising. This research was conducted using a qualitative method by collecting data through interviews and research on the Kitabisa.com website and comparing the results of the literature study with the reality in the field. Also collect supporting data with issues raised. Based on the results of data analysis, it was concluded that the online-based management of zakat, infak and alms at the Kitabisa.com startup can be accessed by everyone with terms and conditions applicable, while the management of funds is carried out transparently, using fundraising and donation methods. The online management of zakat, infak and alms through the Kitabisa.com startup is in accordance with the Muamalah Fiqh perspective.